2007
DOI: 10.1128/aac.00846-07
|View full text |Cite
|
Sign up to set email alerts
|

Mupirocin-Resistant, Methicillin-Resistant Staphylococcus aureus Strains in Canadian Hospitals

Abstract: Mupirocin resistance in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
2
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(111 citation statements)
references
References 48 publications
1
103
2
5
Order By: Relevance
“…Consequently, the reasonable use of disinfectant in hospitals is necessary and justifiable. Mupirocin resistance in S. aureus, especially in MRSA, has been reported in many studies (McNeil et al, 2011;Simor et al, 2007). McNeil et al (2011) showed that 11 % of S. aureus isolates carried the mupA gene and that the gene was more frequent in MSSA isolates than in MRSA isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the reasonable use of disinfectant in hospitals is necessary and justifiable. Mupirocin resistance in S. aureus, especially in MRSA, has been reported in many studies (McNeil et al, 2011;Simor et al, 2007). McNeil et al (2011) showed that 11 % of S. aureus isolates carried the mupA gene and that the gene was more frequent in MSSA isolates than in MRSA isolates.…”
Section: Discussionmentioning
confidence: 99%
“…24 Although the use of cannabinoids as systemic antibacterial agents awaits rigorous clinical trials and an assessment of the extent of their inactivation by serum, 25 their topical application to reduce skin colonization by MRSA seems promising, since MRSA resistant to mupirocin, the standard antibiotic for this indication, are being detected at a threatening rate. 26 Furthermore, since the cannabinoid anti-infective chemotype seems remarkably tolerant to modifications in the prenyl moiety, semipurified mixtures of cannabinoids could also be used as cheap and biodegradable antibacterial agents for cosmetics and toiletries, providing an alternative to the substantially much less potent synthetic preservatives, many of which are currently questioned for their suboptimal safety and environmental profile.…”
Section: Resultsmentioning
confidence: 99%
“…9,31,32 Mupirocin resistance has been reported in some studies of MRSA decolonization, 9,30 but not all such studies. 8,[32][33][34][35] MRSA resistance to chlorhexidine lacks a standard definition, but recent reports suggest that resistant strains are rare in the United States. 36,37 A gene encoding a multidrug efflux pump that is active against chlorhexidine has been reported in MRSA, 38 but its clinical significance is not understood.…”
Section: Discussionmentioning
confidence: 99%